Small fiber damage in patients with chemo-induced polyneuropathy - O. A. Tikhonova; D. S. Druzhinin; O. P. Tuchina; A. V. Vinogradova; S. A. Doktorova; M. I. Dolgaleva; A. M. Tynterova (Нервно-мышечные болезни)
Background. The development of neuropathic pain in chemotherapy‑induced polyneuropathy, is one of the complications of chemotherapy (CT). Especially often it develops after treatment with platinum and taxane drugs. The lesion of thin fibers is an important component of the painful form of polyneuropathy. Since electroneuromyographic examination does not confirm the lesion of thin nerve fibers, this diagnosis is often difficult to confirm in clinical practice, based mainly on subjective assessment of complaints, sensitivity, and the use of questionnaires. Skin biopsy is a validated method for determining intraepidermal nerve fiber density and can be considered for the diagnosis of distal sensory neuropathy, especially small fiber neuropathy. Given the difficulty in assessing small fiber damage, the prevalence and pathophysiology of small fiber neuropathy in cancer patients remain poorly understood.Aim. To evaluate the changes in the number of thin fibers in patients with chemotherapy‑induced polyneuropathy and oncological diseases of the gastrointestinal tract (GIT) and pelvic organs (PO), as well as to analyze the relationship of fiber density with clinical and neurophysiological parameters and neuropathic pain syndrome.Materials and methods. The study included 34 patients over 18 years old, divided equally into two groups: the first group – patients with GIT organs cancer, in which oxaliplatin was the main drug; the second group – patients with PO cancer, in which paclitaxel/docetaxel was the main drug. Patients were examined before and after CT. Exclusion criteria were the presence in the history of complaints that allowed suspecting pathologic conditions potentially capable of causing peripheral nerve damage. All patients underwent electroneuromyography with SRAR index calculation and skin biopsy, as well as assessment of neuropathic pain using scales (National Cancer Institute Common Terminology Criteria for Adverse Events version 5.0, Visual Analogue Scale) and questionnaires (Douleur Neuropathique en 4 Questions, Small fiber neuropathy – symptoms inventory questionnaire). Statistical processing was performed using the GraphPad Prism 8.0.1 program package. Quantitative variables were evaluated using the Kolmogorov–Smirnov test. Correlation analysis between intraepidermal nerve fiber density clinical scales and neurophysiological data was evaluated using Spearman coefficient.Results. 31 patients (14 patients with GIT organs cancer, 17 patients with PO cancer) completed the full cycle of examination before and after СT, 3 patients with GIT organs cancer dropped out of the study due to death. The mean age was 58.0 ± 11.5 years (23–70 years), of which elderly patients (over 60 years old) were 16 (51 %). Wilcoxon signed rank test for pairs showed a significant difference between intraepidermal nerve fiber density in the group of patients with GIT organs cancer before and after CT (p = 0.02), and no significant difference in patients with PO cancer before and after CT (p = 0.37). Statistically significant differences in the amplitude of the sensory potential (S‑response) of the superficial peroneal nerve in patients with PO cancer (p p = 0.0002) and of the calf nerve in patients with PO cancer (p = 0.0001) and GIT organs cancer (p = 0.0017) before and after CT were obtained. Also, SRAR index before and after CT showed a significant difference for both PO (p = 0.0017) and GIT organs cancer (p = 0.0245). Spearman correlation analysis found no significant correlations between intraepidermal nerve fiber density density and the results of electroneuromyography as well as major scales.Conclusion. Small fiber neuropathy is part of mixed sensory neuropathy in patients with chemotherapy‑induced polyneuropathy and occurs more often with the use of oxaliplatin in patients with GIT organs cancer. Identification of patients with pain symptoms and the presence of small fiber neuropathy in the future will help develop an individual approach to the management of this group of patients, and the wider use of skin biopsy techniques will help in the study of reinnervation processes, which is especially important in the development of new therapeutic targets aimed at eliminating nerve damage.